Online Islamic knowledge sources and their authority in Islamic learning: a case study of Indonesian Muslim universities - Askar Askar; Nurdin Nurdin; Adawiyah Pettalongi; Sagaf S. Pettalongi; Jumri H. I. Thahang Basire (Cogent Education)
This study investigates the emergence of new Islamic knowledge authorities in an Islamic learning context. This study used a qualitative method in which the data was gathered through field observation, in-depth interviews, and written document analysis. In-depth interviews involved sixteen students and six Islamic education teachers from two Islamic universities in Indonesia. Data was analyzed using a thematic approach. The approach allowed this study to analyze classification and present themes related to our empirical data analysis. The data analysis was iteratively begun with open coding, selective coding, and theoretical findings. This study found that Indonesian Muslim students view Islamic organizations’ websites, Muslim scholars’ web pages, social media, and Internet memes as new sources of Islamic knowledge. Our findings highlight an important point: online Islamic knowledge sources have become new Islamic knowledge authorities for Indonesian Muslim students. We conclude that new Islamic authorities have emerged through various platforms on the Internet, such as Islamic organization websites, Muslim scholar webpages, social media, and Internet memes. Further research should focus on the implications of online Islamic knowledge sources for Islamic teaching and learning at universities.